Dynamics of the tractor (4x2), and the occurrence of parasitic power circulation in the drive (4x4) - Petrović Predrag T.; Petrović Živojin P.; Obradović Dragoljub M.; Petrović Marija P. (Tehnika, 2015)
When moving tractors with four-wheel drive (4x4) adhesion is achieved by utilization of the entire weight of the vehicle in relation to the movement of vehicles with two-wheel drive (4x2), when the exploitation only part of the weight of the vehicle, which is transmitted through the two operating point. Pulling characteristics in both variants depend on the achievement of optimum. In case that there is a incompatibility of kinematic movement of one wheel, relative to the second drive axle, and in certain types of transmissions, so-called. blocked by divorce, there is the possibility of useless forces or parasitic power, which not only does not participate in the implementation of the tractor, but is opposed to his where aborts conditions of movement of the wheels and the contact surface. In this paper, we give a short overview of the dynamics of movement of the tractor on the rise, with the drive (4x2) and review the possibility of parasitic forces in the drive (4x4) and the effect that created such a power could result in the tractor.